Exploring the Role of ARABIDOPSIS HISTIDINE PHOSPHOTRANSFERASE 4 (AHP4) in Cytokinin Signalling - Chrysanthou, Elina (2023)
Plant hormones are key players in providing the communication signals necessary for plants to coordinate growth, development and respond to environmental stimuli. Among them cytokinins are now widely studied and understood. Cytokinins are being perceived by cells through a two-component His-Asp phosphorelay system where histidine kinases receive the phosphoryl group, histidine phosphotranfer proteins (HPts) convey the signal to response regulators which in turn, activate or inhibit cytokinin inducible genes. In Arabidopsis, four of the HPts (AHP1, 2, 3, 5) are well characterised for their redundant role in cytokinin signalling but the function of AHP4 remains a mystery. In this work, I investigate the role of AHP4 in Arabidopsis using a combination of molecular, biochemical, and physiological approaches. Phylogenetic analysis reveals that AHP4 is conserved across angiosperms, and it forms a distinct clade very closely related to known monocot cytokinin signalling inhibitors. Functional modelling analysis of all AHPs show that AHP4 might not be able to function as an HPt due to positional effect of its conserved His region. Consistent with this, ahp4 plants exhibit subtle phenotypes attributed to cytokinin responses suggesting a minor role in cytokinin signalling. However, the sensitivity of ahp4 plants observed under osmotic stress, and the upregulation of AHP4 in water limiting conditions, suggest a novel function of AHP4 in root drought tolerance. Here I show that AHP4 is essential to preserve the primary root meristem in drought stress conditions through the maintenance of phloem transport.